Annealing Effect on the Optical Properties of (CdO)1-x (Mg)x Thin Films (Journal of the College of Basic Education, 2022)
(CdO)1-x (Mg)x thin films with (x = 0.06) deposited on perheated glass substrates at temperature 350°C by chemical spray pyrolysis technique. We have studied the effect of annealing temperature at (400, 450) °C. Optical absorption studies in the wavelength range 300–900 nm in order to calculate the optical constants such as refractive index, extinction coefficient, real and imaginary parts of dielectric constant. Results illustrate that the refractive index decreased at 600 nm while the extinction coefficient slightly increases after annealing, on the other hand, the values of real and imaginary parts of the dielectric are found to be decreases with increasing annealing. The skin depth is found to be decreases as the annealing temperature increased to 450 °C, so the skin depth is a transmittance related.